CHANGING THE PARADIGM OF STATES IN THE RABIC MIDDLE EAST REGION BRINGS AUTHORITARIANISM TOWARDS DEMOCRACY - Muhrim Djakat,; Misbahuddin, Misbahuddin; Kurniati, Kurniati (International Journal of Social Science, 2023)
The demonstration phenomenon that was launched by the Arab Spring has caused political upheaval in Middle Eastern countries, starting from Tunisia, Egypt, Libya, Yemen, and Syria which is still continuing today, is a bridge to change, the fall of authoritarian regimes, and also as a symbol of struggle pro-democratic Arab people who demand a paradigm shift in the Middle East state. The intended change is in the economic, social, open and democratic aspects of the political system. The Arab Spring phenomenon still leaves many problems, Middle Eastern countries are still in a slump, trapped in conflict and civil war. The democratic transition that was aspired to did not go well, being held hostage by the interests of authoritarian and sectarian regimes: ethnicity, religion, sects and political groups. Authoritarianism is one of the causes of instability and has colored the political dynamics of the Middle East. Socio-historically, authoritarianism and sectarianism in the Middle East have multi-layered roots over a long period of time. This paper tries to read the paradigm shift in the Arab region state state against authoritarianism towards democracy